Advances in targeted therapies for systemic sclerosis - Rong XIAO; Jiani LIU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Systemic sclerosis (SSc), as an immune-mediated chronic connective tissue disease, is mainly characterized by fibrosis of multiple organs, including the skin and lungs. It is a rare disease, with a high incidence and mortality among rheumatic immune diseases. At present, there is no effective drug for the treatment of SSC. In recent years, it has been found that the interactions between T/B lymphocytes, fibroblasts, endothelial cells, and various pro-inflammatory and fibrotic signaling molecules play a crucial role in the occurrence and development of SSc. On this basis, a series of targeted drugs are currently being tested. CD20 monoclonal antibodies (Rituximab), IL-6 receptor antagonists (Tocilizumab), and multi-target tyrosine kinase inhibitors (Nintedanib) have been approved for the treatment of SSc or SSc-ILD by FDA. In addition, other targeted drugs such as Janus kinase inhibitors and various interleukin inhibitors have shown preliminary therapeutic potentials through clinical trials. This article reviews the research progress in targeted therapies for SSc by synthesizing the latest evidence from four aspects: targeting B lymphocytes, T lymphocytes, vascular endothelial cells, and pro-inflammatory and fibrotic signaling molecules.